Genetic variation in plant CYP51s confers resistance against voriconazole, a novel inhibitor of brassinosteroid-dependent sterol biosynthesis. - Wilfried Rozhon; Sigrid Husar; Florian Kalaivanan; Mamoona Khan; Markus Idlhammer; Daria Shumilina; Theo Lange; Thomas Hoffmann; Wilfried Schwab; Shozo Fujioka; Brigitte Poppenberger (PLoS ONE)
Brassinosteroids (BRs) are plant steroid hormones with structural similarity to mammalian sex steroids and ecdysteroids from insects. The BRs are synthesized from sterols and are essential regulators of cell division, cell elongation and cell differentiation. In this work we show that voriconazole, an antifungal therapeutic drug used in human and veterinary medicine, severely impairs plant growth by inhibiting sterol-14α-demethylation and thereby interfering with BR production. The plant growth regulatory properties of voriconazole and related triazoles were identified in a screen for compounds with the ability to alter BR homeostasis. Voriconazole suppressed growth of the model plant Arabidopsis thaliana and of a wide range of both monocotyledonous and dicotyledonous plants. We uncover that voriconazole toxicity in plants is a result of a deficiency in BRs that stems from an inhibition of the cytochrome P450 CYP51, which catalyzes a step of BR-dependent sterol biosynthesis. Interestingly, we found that the woodland strawberry Fragaria vesca, a member of the Rosaceae, is naturally voriconazole resistant and that this resistance is conferred by the specific CYP51 variant of F. vesca. The potential of voriconazole as a novel tool for plant research is discussed.